2021
DOI: 10.21608/ejhm.2021.189618
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Pattern in Patients with Systemic Lupus Erythematosus with and without Nephritis

Abstract: Background: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease where chronic inflammation and organ damage is observed due to various suspected causes e.g. inadequate levels of vitamin D (a steroid hormone with immunomodulatory effects). Objective: To assess vitamin D (VD) levels in serum of patients with lupus nephritis (LN) in comparison with patients with extra-renal lupus and healthy controls, and to assess the relation between VD levels and the various clinical and laboratory disease para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
(2 reference statements)
3
1
0
Order By: Relevance
“…This present study showed a significant increase in CRP level in SLE group than control group. This agreed with many studies which reported higher CRP in SLE group than normal persons [10,11] . Regarding Immunological markers, ANA level was significantly increased in SLE group contrasted to control group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This present study showed a significant increase in CRP level in SLE group than control group. This agreed with many studies which reported higher CRP in SLE group than normal persons [10,11] . Regarding Immunological markers, ANA level was significantly increased in SLE group contrasted to control group.…”
Section: Discussionsupporting
confidence: 93%
“…This study showed that ESR was significantly increased in SLE group compared to control group. This agreed with several studies which reported higher ESR in SLE group than normal persons, which might be due to increased fibrinogen in the acute phase response of the disease activity [10,11,13] . This present study showed a significant increase in CRP level in SLE group than control group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations